Death Penalty, Right to Life, and Various Controversies in Human Rights - Adi Saputra; Febrian Jadug Santoso (Universitas Negeri Semarang, 2019)
In Indonesia, the issue of capital punishment is a matter of controversy between those who are pro to the death penalty and those who are against the death penalty. Those who disagree with the death penalty assume that the inhuman death sentence is contrary to the principle of fair and civilized humanity in accordance with Pancasila, only Allah can take a person's life, if the judge is wrong in passing the sentence, what can be improved again. The pro-death penalty party considers that the death penalty deserves to be imposed on a sadistic criminal in carrying out his action because if he is not sentenced to death he will repeat his crime. The death penalty is also in accordance with the National RKUHP which is pro on capital punishment, but with certain conditions. If we observe from existing laws such as the Narcotics Act, the Corruption Law, the Terrorist Law, etc. then it can be said that the Law is pro death sentence. In the context of capital punishment, Kontras, which is concerned with the matter of upholding human rights, provides a criminological view that capital punishment does not provide a deterrent effect on the perpetrators of Extraordinary Crimes, because such actions can be motivated, not only from individual distributor factors, but also structural factors, for example community economic instability due to domestic political conditions. So, because the death penalty also conflicts with the right to life, it is fitting that the death penalty be replaced with life imprisonment.